Extracellular matrix in tumor biology - Brekken, Rolf A.; Stupack, Dwayne (Springer, 2017)
This volume provides an overview on the influence of Extracellular Matrix (ECM) on tumor progression. It covers topics such as signaling induced by structural ECM proteins including collagen and fibronectin, the control of ECM deposition and the turnover in tumors. Also discussed are the migration of cells through basement membranes and the function of proteoglycans including lumican and veriscan in tumor progression. Biomaterial-based in-vitro models as well as C. elegans models of the tumor microenvironment are used to show how these models can lead to a greater understanding of the disease mechanisms that promote cancer progression. The book addresses researchers working on cancer biology or ECM, and oncologists alike.
Keywords: Extracellular matrix.; Tumors.; elektronické knihy; electronic books